2021
DOI: 10.3390/fermentation7040250
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, Volatile Compounds, Microbiological and Organoleptical Characteristics of Low-Fat Buffalo Milk Yogurt Enriched with Whey Protein Concentrate and Ca-Caseinate during Cold Storage

Abstract: Yogurt is a popular fermented milk product across the world. Structure, taste, and odor characteristics are created by fermenting yogurt with diverse ingredients and lactic acid bacteria (LAB), which contribute the most to the acceptance and quality of yogurt. In this study, low-fat buffalo milk yogurts (LFBY) were produced with the enrichment of 1% (w/w) whey protein concentrate (WPC) and Ca-caseinate (Ca-CN). Yogurts were analyzed based on microstructural, microbiological, organoleptical properties; volatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“… Atallah et al (2020) reported that the addition of WPC and Ca-CN accelerates LAB growth in low-fat yogurts. Recently, Barakat et al (2021) also reported that buffalo milk yogurts enriched with WPC and Ca-CN exhibited a higher viable count of Lactobacillus delbrueckii ssp. bulgaricus and S. thermophiles than the control yogurt sample.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“… Atallah et al (2020) reported that the addition of WPC and Ca-CN accelerates LAB growth in low-fat yogurts. Recently, Barakat et al (2021) also reported that buffalo milk yogurts enriched with WPC and Ca-CN exhibited a higher viable count of Lactobacillus delbrueckii ssp. bulgaricus and S. thermophiles than the control yogurt sample.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, MPC can be used to increase the protein content and improve the texture and stability of yogurts ( Agarwal et al, 2015 ; Uluko et al, 2016 ). Some researchers have reported that milk proteins can lead to the production of volatile aroma compounds in cultured dairy products, such as yogurt ( Barakat et al, 2021 ; Martin et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, probiotics contained beneficial bacteria that benefit human health, combined with CM formulating FCM due to their synergic effects, which are highly desirable [63,64]. In the development of probiotic drinks, particular strains based on functional criteria and basal environment should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional fermented dairy product, yoghurt is favoured by consumers because of the unique flavour and rich nutrition; meanwhile, it is regarded as a carrier for probiotic (Hthn et al ., 2020; Atallah, 2021). Numerous researches indicated that yoghurt can abate allergenicity.…”
Section: Introductionmentioning
confidence: 99%